A Design of Standalone Hybrid PV/Wind/Fuel cell Generation System and Hydrogen Electrolyzer With Local Controller for Remote Areas - Soedibyo Soedibyo; Sjamsjul Anam; Andri Pradipta (Department of Electrical Engineering ITS and FORTEI, 2019)
Integration of fuel cell and electrolyzer on DC bus is a promising alternative to solve voltage fluctuation and balance of power problems in a standalone hybrid renewable power generation systems. The hybrid renewable power generation systems consist of photovoltaic, wind turbine, fuel cell and hydrogen electrolyzer. Each the component integrated on DC bus through the converter DC – DC using local controller to supply the inverter which connected to the islanded load. Local controller in each part will make the system become flexible if there are additional generating units in the future. The local control methods used in this hybrid renewable power generation system is MPPT and constant voltage control. MPPT control applied to photovoltaic and wind turbine converters to maximize power generation from photovoltaic and wind turbine. Constant voltage controller applied to the fuel cell and electrolyzer converters to control the DC bus voltage alternately. This research is a new design system for remote areas by utilizing the potensial of renewable energy in the area. The result show the power quality and continuity of electricity services.Keywords: hybrid, hydrogen electrolyzer, fuel cell, local controller, photovoltaic, wind turbine.